Mutations and deletions of the TP53 gene predict nonresponse to treatment and poor outcome in first relapse of childhood acute lymphoblastic leukemia - Hof, Jana; Krentz, Stefanie; van Schewick, Claudia; Körner, Gabriele; Shalapour, Shabnam; Rhein, Peter; Karawajew, Leonid; Ludwig, Wolf-Dieter; Seeger, Karl; Henze, Günter; von Stackelberg, Arend; Hagemeier, Christian; et al. (Journal of clinical oncology, 2011)
In the clinical management of children with relapsed acute lymphoblastic leukemia (ALL), treatment resistance remains a major challenge. Alterations of the TP53 gene are frequently associated with resistance to chemotherapy, but their significance in relapsed childhood ALL has remained controversial because of small studies. Therefore, we systematically studied 265 first-relapse patients enrolled in the German Acute Lymphoblastic Leukemia Relapse Berlin-Frankfurt-Mü nster 2002 (ALL-REZ BFM 2002) trial for sequence and copy number alterations of the TP53 gene by using direct sequencing and multiplex ligation-dependent probe amplification. We observed copy number and sequence alterations of TP53 in 12.4% (27 of 218) of patients with B-cell precursor ALL and 6.4% (three of 47) of patients with T-cell ALL relapse. Backtracking to initial ALL in 23 matched samples revealed that 54% of all TP53 alterations were gained at relapse. Within B-cell precursor ALL, TP53 alterations were consistently associated with nonresponse to chemotherapy (P < .001) and poor event-free survival (P < .001) and overall survival rates (P = .002). TP53 alterations also had a significant impact on survival within intermediate-risk (S2) and high-risk (S3/S4) relapse patients (P = .007 and P = .019, respectively). This prognostic significance of TP53 alterations was confirmed in multivariate analysis. Besides their clinical impact, TP53 alterations were associated with a higher fraction of leukemic cells in S/G(2)-M phase of the cell cycle at relapse diagnosis. Alterations of the TP53 gene are of particular importance in the relapse stage of childhood ALL, in which they independently predict high risk of treatment failure in a significant number of patients. Therefore, they will aid in future risk assessment of children with ALL relapse.